2015
DOI: 10.1039/c5sc00814j
|View full text |Cite
|
Sign up to set email alerts
|

A highly convergent synthesis of the C1–C31 polyol domain of amphidinol 3 featuring a TST-RCM reaction: confirmation of the revised relative stereochemistry

Abstract: The concise enantioselective synthesis of the revised C1–C31 fragment of the polyketide amphidinol 3 was accomplished in 16 steps and 12.8% overall yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…13 Hence, there is a degree of predictability with this process, which makes it an attractive strategy for applications to target-directed synthesis. 9 The ability to construct contiguous stereogenic centers, especially polypropionate and polyol derivatives, is potentially useful in the preparation of complex synthetic intermediates. In order to illustrate the synthetic utility of the …”
Section: Syn Thesismentioning
confidence: 99%
See 2 more Smart Citations
“…13 Hence, there is a degree of predictability with this process, which makes it an attractive strategy for applications to target-directed synthesis. 9 The ability to construct contiguous stereogenic centers, especially polypropionate and polyol derivatives, is potentially useful in the preparation of complex synthetic intermediates. In order to illustrate the synthetic utility of the …”
Section: Syn Thesismentioning
confidence: 99%
“…These results highlight the generality of the TST-RCM transformation, which facilitates the union of more elaborate fragments relevant to target-directed synthesis. 9 Hence, with the library of silaketals in hand, we elected to examine the stereoselective hydroboration reaction (Table 2). Interestingly, this study demonstrated that silaketals 7a,c reacted with borane-dimethyl sulfide complex to afford the secondary alcohols 8a,c in excellent yield and selectivity (rs ≥19:1, ds ≥19:1) after oxidative work-up (entries 1 and 3); however, the analogous process with silaketals 7b,d resulted in poor regio-and modest diastereocontrol.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, all of them were based on the originally proposed structure reported in 1999. Therefore, there was no argument regarding the stereochemistry of AM3 except for the synthetic study of the C1–C31 polyol fragment, by the group of Evans, based on the revised structure in 2013.…”
Section: Figurementioning
confidence: 99%
“…The stereochemical structure elucidation and efforts toward total synthesis have generated significant interest in recent years. [6][7][8][9] Amphidinol 3 has demonstrated potent antifungal activity with submicromolar IC50 values and relatively potent hemolytic activity (EC50 = 0.25 μM/kg), with its mode of action attributed to increasing ion permeability in biomembranes from the formation of pores or lesions. [10][11] The stambomycin family of compounds all contain 1,5,7-triol motifs (Figure 1.4).…”
mentioning
confidence: 99%